CLASHING PERSPECTIVES FOR THE EXISTENCE OF HAMAS IN THE ISRAEL-PALESTINE CONFLICT: INDEPENDENCE SUPPORTING GROUPS OR TERRORIST GROUPS RESULTING FROM WESTERN RHETORIC - Darmayadi, Andrias; Nur , Katie; Nainggolan, Evi Novrisari; Putri, Risa Hazkiasyah; Zahra, Nabila Nurul (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to describe and compare the two perspectives in viewing the Hamas group from the perspective of Palestinian society and Western countries . The view of Hamas as a pro-Palestinian independence group or a terrorist group due to Western rhetoric is a fairly common opinion where the history of the Israeli-Palestinian conflict and the judgment against Hamas are strongly influenced by political perspectives and geopolitical interests. This research uses qualitative methods which aim to describe how International perspective on Hamas and the influence of the emergence of two perspectives and points of view on Hamas. The results of this research show that the pattern of military resistance carried out by Hamas against Israel causes very contradictory perspectives in describing Hamas. The conclusion of this research is that the point of view towards Hamas is also greatly influenced by the political background, history and national interests of a country so that The debate about whether Hamas is a group that protects Palestinian independence or a terrorist group is still ongoing and has not yet reached a universal international context.